KONTEKS PENUTURAN PANTUN PADA ADAT PERKAWINAN MELAYU KEPULAUAN RIAU - Rezki Puteri Syahrani Nurul Fatimah; Franscy Franscy (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract: From the various traditions that exist in Malay society, the tradition of wedding customs is a tradition that is often found, especially in the coastal areas of Riau. Wedding custom uses literary work as a medium of communication in the arrangement of its program. Malay society of Daik Lingga believes that this literary work increases knowledge about the values of life. The correlation between literary work and the wedding custom from the Malay society of Daik Lingga, Riau Archipelago, is illustrated by the things that are expressed in the art and literature, both oral and written literature. The aim of this research is to conduct a study and analysis of speech context that contained in Pantun as the wedding custom of Riau Archipelago society The research method used by researchers is a descriptive analysis method. The research data was taken from the wedding custom from the Malay society of Daik Lingga, Riau Archipelago, specifically related to traditional poetry that is used as the research object. The aspects that researchers examined in the speech context of Pantun include the Situation Context and Cultural Context. Results of the data indicated that Pantun in the wedding custom from Malay society of Daik Lingga, Riau archipelago contained speech context which is divided into the Situation Context (time, place, and Situation) and Cultural Context (geographical location, economic equality, social welfare, religion, culture, customs, and arts). Abstrak: Tradisi yang masih ada dalam masyarakat Melayu khususnya di wilayah pesisir Riau adalah tradisi adat perkawinan. Tradisi ini dilestarikan oleh masyarakat Melayu Daik Lingga. Dalam tradisi tersebut, karya sastra dalam bentuk pantun digunakan sebagai media komunikasi pada tatanan acaranya. Mereka meyakini bahwa karya sastra tersebut menambah pengetahuan tentang nilai-nilai kehidupan. Tujuan penelitian ini adalah untuk melakukan kajian dan analisis tentang konteks penuturan yang ada dalam pantun sebagai media komunikasi dalam adat perkawinan masyarakat Kepulauan Riau. Metode penelitian yang digunakan oleh peneliti adalah metode analisis deskriptif. Data penelitian diambil dari adat pernikahan dari masyarakat Melayu Daik Lingga, Kepulauan Riau. Aspek-aspek yang diteliti dalam konteks penuturan pantun mencakup konteks situasi dan konteks budaya. Hasil penelitian menunjukkan bahwa pantun dalam adat pernikahan berisi konteks penuturan yang dibagi menjadi konteks situasi (waktu, tempat, dan situasi) dan konteks budaya (lokasi geografis, kesetaraan ekonomi, kesejahteraan sosial, agama, budaya, adat, dan seni).